2008
DOI: 10.1111/j.1462-2920.2007.01501.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenazines and biosurfactants interact in the biological control of soil‐borne diseases caused by Pythium spp.

Abstract: In this study, the putative role of phenazines and rhamnolipid-biosurfactants, antagonistic metabolites produced by Pseudomonas aeruginosa PNA1, was tested in the biological control of Pythium splendens on bean (Phaseolus vulgaris L) and Pythium myriotylum on cocoyam (Xanthosoma sagittifolium L Schott). A rhamnolipid-deficient and a phenazine-deficient mutant of PNA1 were used either separately or jointly in plant experiments. When the mutants were applied separately, no disease-suppressive effect was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
58
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(60 citation statements)
references
References 45 publications
(55 reference statements)
2
58
0
Order By: Relevance
“…Since this discovery, many studies have shown that P. fluorescens 2-79 and other phenazine-producing (Phz + ) strains are effective biocontrol agents against common agriculturally significant soil-borne fungal pathogens (including Rhizoctonia, Fusarium, G. graminis var. tritici, and Pythium) when applied to seeds before planting [4,[6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Since this discovery, many studies have shown that P. fluorescens 2-79 and other phenazine-producing (Phz + ) strains are effective biocontrol agents against common agriculturally significant soil-borne fungal pathogens (including Rhizoctonia, Fusarium, G. graminis var. tritici, and Pythium) when applied to seeds before planting [4,[6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…They show potential applications in the biocontrol of Grampositive and Gram-negative bacteria, yeast, and fungi (Abalos et al, 2001;Kahraman and Erenler, 2012), and also insects as well (Kim et al, 2011). In particular, rhamnolipids can effectively control some plant pathogens such as Phytium aphanidermatum, Pythium splendens, Pythium myriotylum, Phythophthora capsici, Plasmopara lactucae-radicis and Colletotrichum orbiculare (Kim et al, 2000;Perneel et al, 2008;Stanghellini and Miller, 1997). Furthermore, they can induce plants to generate defense responses against fungal infections (Varnier et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…They have recently been shown to elicit plant defense responses and to induce resistance against B. cinerea in grapevine (Vitis vinifera; Varnier et al, 2009). They also participate to biocontrol activity of the plant beneficial bacteria Pseudomonas aeruginosa PNA1 against oomycetes (Perneel et al, 2008). However, the signaling pathways used by RLs to stimulate plant innate immunity are not known.…”
mentioning
confidence: 99%